Entrepreneurial resourcefulness in unstable institutional contexts: The example of European Union borderlands. (23rd October 2017) - Welter, Friederike; Xheneti, Mirela; Smallbone, David
Abstract : Research Summary: This article advances our understanding of entrepreneurial resourcefulness in unstable institutional contexts, which are characterized by resource constraints and institutional changes but are rich in intangible resources of a sociocultural nature. Drawing on qualitative data of individuals engaged in informal cross‐border activities in EU borderlands, we theorize resourcefulness along two core dimensions: continuity and change in relation to sociocultural, spatial, and institutional conditions and development and coping as outcomes. We identify six configurations of resourcefulness patterns and outcomes that extend current understandings of the variations in how individuals interact with their contexts, offering a nuanced view of resourcefulness. Managerial Summary: This article aims to understand entrepreneurial resourceful behavior in contexts characterized by difficult economic conditions and institutional changes. We use qualitative data of individuals involved in informal cross‐border activities in EU borderlands that have undergone the collapse of communism and EU enlargement rounds. The data shows that resourcefulness relies on continuity, reflected in previous skills and networks, family and friends, or common cultural understandings and change, as resourcefulness where individuals implicitly or explicitly challenge the new border regulations. Individuals' resourcefulness translates into " coping " outcomes, as in achieving a minimal income to maintain the current way of life and/or to sustain social relationships and " development " outcomes, whereby individuals earn more income and improve their business activities.